Self‐gated fetal cardiac MRI with tiny golden angle iGRASP: A feasibility study. Issue 1 (2nd February 2017) - Haris, Kostas; Hedström, Erik; Bidhult, Sebastian; Testud, Frederik; Maglaveras, Nicos; Heiberg, Einar; Hansson, Stefan R.; Arheden, Håkan; Aletras, Anthony H.
Abstract : Purpose: To develop and assess a technique for self‐gated fetal cardiac cine magnetic resonance imaging (MRI) using tiny golden angle radial sampling combined with iGRASP (iterative Golden‐angle RAdial Sparse Parallel) for accelerated acquisition based on parallel imaging and compressed sensing. Materials and Methods: Fetal cardiac data were acquired from five volunteers in gestational week 29–37 at 1.5T using tiny golden angles for eddy currents reduction. The acquired multicoil radial projections were input to a principal component analysis‐based compression stage. The cardiac self‐gating (CSG) signal for cardiac gating was extracted from the acquired radial projections and the iGRASP reconstruction procedure was applied. In all acquisitions, a total of 4000 radial spokes were acquired within a breath‐hold of less than 15 seconds using a balanced steady‐state free precession pulse sequence. The images were qualitatively compared by two independent observers (on a scale of 1–4) to a single midventricular cine image from metric optimized gating (MOG) and real‐time acquisitions. Results: For iGRASP and MOG images, good overall image quality (2.8 ± 0.4 and 2.6 ± 1.3, respectively, for observer 1; 3.6 ± 0.5 and 3.4 ± 0.9, respectively, for observer 2) and cardiac diagnostic quality (3.8 ± 0.4 and 3.4 ± 0.9, respectively, for observer 1; 3.6 ± 0.5 and 3.6 ± 0.9, respectively, for observer 2) were obtained, with visualized myocardial thickening over the cardiac cycle and well‐defined myocardial borders to ventricular lumen and liver/lung tissue. For iGRASP, MOG, and real time, left ventricular lumen diameter (14.1 ± 2.2 mm, 14.2 ± 1.9 mm, 14.7 ± 1.1 mm, respectively) and wall thickness (2.7 ± 0.3 mm, 2.6 ± 0.3 mm, 3.0 ± 0.4, respectively) showed agreement and no statistically significant difference was found (all P > 0.05). Images with iGRASP tended to have higher overall image quality scores compared with MOG and particularly real‐time images, albeit not statistically significant in this feasibility study ( P > 0.99 and P = 0.12, respectively). Conclusion: Fetal cardiac cine MRI can be performed with iGRASP using tiny golden angles and CSG. Comparison with other fetal cardiac cine MRI methods showed that the proposed method produces high‐quality fetal cardiac reconstructions. Level of Evidence: 2 Technical Efficacy: Stage 1 J. MAGN. RESON. IMAGING 2017;46:207–217